Effects of Parenting Skills Training Program for Aggressive Behavior Reduction among School-aged Children: A Quasi-Experimental Study - Bhusiri, Pimsiri; Phuphaibul, Rutja; Suwonnaroop, Nantawon; Viwatwongkasem, Chukiat (Pacific Rim International Journal of Nursing Research, 2018)
Worldwide, improper parenting practices may induce behavioral problems in children, especially aggressive behavior. This quasi-experimental study examined the effects of a Parenting Skills Training Program on parents’ intentions, and behaviours regarding modifying their sixth graders’ aggressive behavior. Two secondary schools with similar contexts in Bangkok were purposively selected to be the experimental and comparison schools. Students with high aggressive behavioural scores were identified and recruited, as well as their parents into the study. Parents of students in the experimental group received five weekly two-hour lessons of parenting skills training, whereas the comparison group did not receive the training. The parents’ intentions and behaviors regarding their child’s aggressive behavior modification were measured by a self- reported questionnaire and their child’s aggressive behaviors were assessed as well. Results revealed that the parents in the experimental group had statistically significant higher mean scores of intentions and children’s aggressive modification behavior across all time points of measurements than those in the comparison group. Compared to the comparison group, the experimental group also had a statistically significant reduction of childrens’ aggressive behaviour at one week and one month after the Program. Nurses can apply this parenting skills training program to train the parents of school-aged children regarding aggressive behavior in the schools, childcare centers, pediatric units and communities with similar characteristics of populations, to prevent aggressive behaviors of their school-age children.